1987
DOI: 10.1136/bmj.295.6612.1516
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of non-tobacco cigarettes.

Abstract: will be to discover the personality characteristics which make some doctors particularly vulnerable to desynchronisation of circadian performance rhythm after disruption of sleep. Data from the Tucson epidemiological study of airways obstructive disease on smoking of non-tobacco cigarettes such as marijuana were analysed to determine the effect of such smoking on respiratory symptoms and pulmonary function. Among adults aged under 40, 14% had smoked non-tobacco cigarettes at some time and 90/o were current use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
110
2
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 15 publications
14
110
2
4
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13] These studies have predominantly involved smokers of herbal cannabis. Evidence from the present study suggests that these effects are also seen with resin cannabis.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12][13] These studies have predominantly involved smokers of herbal cannabis. Evidence from the present study suggests that these effects are also seen with resin cannabis.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Although cannabis use does appear to be associated with greater reported respiratory symptoms, no strong evidence has emerged of deleterious effects on objective measures of respiratory function. [4][5][6][7][8][9][10][11][12][13] The populations studied in this regard have been relatively young and have almost exclusively used herbal (grass or weed made from the dried leaves and flowering part of the female plant and resembling dried herbs) cannabis. In countries such as the UK, resin cannabis (known as 'hash'), smoked in a cigarette prepared with tobacco, known colloquially as a 'joint' and elsewhere as a spliff or reefer, appears to be the most common form of consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies have shown that marijuana use was uniformly associated with an increased prevalence of symptoms of chronic bronchitis (3-7), but the associations with spirometric findings have been less uniform, variably revealing no differences in forced expired volume in 1 s (FEV 1 ) or forced vital capacity (FVC) (3)(4)(5)(6), an actual increase in FVC and/or FEV 1 (8,9), and either a decrease or no change in the FEV 1 /FVC ratio (4,5,7,8,10) when comparisons were made between smokers of marijuana (either alone or adjusted for tobacco) and nonsmokers, as recently reviewed (11).…”
mentioning
confidence: 99%
“…For example, SAD patients with AUD report more severe impairment than patients with SAD without AUD (Schneier et al, 1989) and alcoholics with SAD demonstrate more severe symptoms of alcohol dependence and display more depressive symptomatology than alcoholics without SAD (Thomas et al, 1999b). Cannabis dependence among individuals with SAD is problematic because smoking cannabis has a larger effect on respiratory function than smoking tobacco (Bloom et al, 1987;Sherrill et al, 1991), including cellular changes that may serve as a risk factor for cancer (Fligiel et al, 1997;Sarafian et al, 1999). Long-term cannabis use is associated with legal problems and increased alcohol and tobacco use (Patton et al, 2002;Reilly et al, 1998) and driving under the influence of cannabis leads to increased automobile crash risk (Ramaekers et al, 2004).…”
Section: Introductionmentioning
confidence: 99%